Rokat Kampong: wujud akulturasi Islam dalam budaya lokal - Uswatun Hasanah; Rosyidi Rosyidi (LP2M Universitas Sarjanawiyata Tamansiswa, 2023)
The people of Tojeren Pragaan Daya Pragaan Sumenep hamlet maintain the local cultural values they have received from their ancestors but they also incorporate Islamic elements or activities into their implementation. Islamic activities that exist in these local cultural traditions create a new culture called Rokat Kampong which is a form of cultural acculturation. This research was conducted to see the form of Rokat Kampong implementation in Islamic acculturation. This research is descriptive phenomenological research with data collection through interviews, observation and documentation. The results showed that the community carried out the Rokat Kampong program by incorporating Islamic activities but did not abandon the local cultures they had received from their ancestors. Through various processions of Islamic activities and the slaughtering of goats in this Rokat Kampong program and the burial of heads, kokot of goats with beliefs, certain prayer processions, is evidence of the acculturation of Islam in the local culture. Based on the results of research, it can be concluded that, in Rokat Kampong activities, there are elements of local culture and acculturation of Islamic values that are included in